941. Clinical Outcomes of Vancomycin Area-Under-the-Curve Monitoring: A Quasi-Experimental Study Interim Analysis. (15th December 2022) - Flynn, Ryan; Tucker, Natalie; Foreman, Jena K
Abstract: Background: The 2020 Infectious Diseases Society of America vancomycin guidelines recommend the use of area-under-the-curve (AUC) monitoring instead of trough concentration monitoring. These guidelines changed due to evidence showing decreased rates of nephrotoxicity and lack of correlation between vancomycin troughs and patient treatment outcomes. Two common methodologies of calculating AUC exist in clinical practice, including two level kinetic calculations and Bayesian software programs. Previous studies used two levels for calculating the AUC. The purpose of this study is to evaluate if the same reduction in acute kidney injury (AKI) is achieved while using a Bayesian software program. Methods: This retrospective quasi-experiment was performed at two sites within the same health system. The primary objective of this study was to assess the rate of AKI, as defined by the Acute Kidney Injury Network (AKIN) criteria, between patients receiving vancomycin dosed by trough monitoring as compared to AUC monitoring. Secondary objectives include mean daily dose of vancomycin, number of vancomycin levels, and severity of AKI. Patients were included in the study if they were 18 years or older, with at least one vancomycin concentration drawn. Patients were excluded if they had a baseline serum creatine greater than 2 mg/dL, received renal replacement therapy of any type, or received > 1 doses of vancomycin prior to admission. After screening for inclusion criteria, patients were matched 1:1 based on APACHE II score and vancomycin indication. Results: One hundred and thirty patients met inclusion criteria at the interim analysis. Overall, baseline characteristics were similar between groups. No statistical difference was detected regarding the rate of acute kidney injury between the vancomycin trough group and AUC group (12% vs 14% p=0.971). The mean total daily doses of vancomycin were 1642 mg per day in the AUC group and 1838 mg per day in the trough group (p=0.08). Conclusion: No statistical difference in rates of AKI were detected at the interim analysis, likely due to small sample size. Further data collection is ongoing to meet power and full results will be presented. Disclosures: All Authors : No reported disclosures.